A Missed Partnership: Russia and the US at the Pacific - D. V. Suslov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
Both Russia and the United States consider the Asia-Pacific as the center of the world economy and politics and assume the active presence in the region crucial for their security and economic development. They did not have such sharp contradictions there as in Europe or in the post-Soviet space. Moreover, some of their interests in the Asia-Pacific Region coincide – such as preventing Chinese hegemony. In this regard, the Russian-American dialogue and cooperation in the Asia-Pacific could be an important pillar of the positive agenda of their relations and a factor in their sustainability. Due to foreign policy inertia, the inflexibility of the agenda of Russian-American relations and the inability of the parties to go beyond the usual pattern, such a dialogue has not even begun. Both sides demonstrated strategic myopia. This weakened the resilience of US-Russian relations in the face of new challenges and accelerated their deterioration and disruption to a new confrontation. The Asia-Pacific has become another theater of the US-Russian systemic confrontation. However, it is in the interest of bothRussia and the United States to separate relations in this region from their general confrontation. This will create favorable conditions for Russia to build a balanced partnership system in the Asia-Pacific, which is necessary to consolidate its role as an independent global great power. In addition, the Russian-American dialogue on the Asia-Pacific, or at least the weakening of their confrontation in this region, will reduce its polarization and prevent tensions between the US and its Asian allies and partners.